A comparison of aphasia therapy outcomes before and after a Very Early Rehabilitation programme following stroke. Issue 2 (March 2014) - Godecke, Erin; Ciccone, Natalie A.; Granger, Andrew S.; Rai, Tapan; West, Deborah; Cream, Angela; Cartwright, Jade; Hankey, Graeme J.
Abstract Background Very early aphasia rehabilitation studies have shown mixed results. Differences in therapy intensity and therapy type contribute significantly to the equivocal results. Aims To compare a standardized, prescribed very early aphasia therapy regimen with a historical usual care control group at therapy completion (4–5 weeks post‐stroke) and again at follow‐up (6 months). Methods & Procedures This study compared two cohorts from successive studies conducted in four Australian acute/sub‐acute hospitals. The studies had near identical recruitment, blinded assessment and data‐collection protocols. The Very Early Rehabilitation (VER) cohort (N = 20) had mild–severe aphasia and received up to 20 1‐h sessions of impairment‐based aphasia therapy, up to 5 weeks. The control cohort (n = 27) also had mild–severe aphasia and received usual care (UC) therapy for up to 4 weeks post‐stroke. The primary outcome measure was the Aphasia Quotient (AQ) and a measure of communicative efficiency (DA) at therapy completion. Outcomes were measured at baseline, therapy completion and 6 months post‐stroke and were compared using Generalised Estimating Equations (GEE) models. Outcomes & Results After controlling for initial aphasia and stroke disability, the GEE models demonstrated that at the primary end‐point participants receiving VER achieved 18% greater recovery on the AQ and 1.5% higher DA scores than those in the control cohort. At 6 months, the VER participants maintained a 16% advantage in recovery on the AQ and 0.6% more on DA scores over the control cohort participants. Conclusions & Implications A prescribed, impairment‐based aphasia therapy regimen, provided daily in very early post‐stroke recovery, resulted in significantly greater communication gains in people with mild–severe aphasia at completion of therapy and at 6 months, when compared with a historical control cohort. Further research is required to demonstrate large‐scale and long‐term efficacy.